(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study examines how certification and job motivation affect elementary school teachers’ effectiveness in the Karang Agung Ilir District. 60 certified teachers served as samples for quantitative descriptive approaches. Surveys and interviews were used to gather data, which was then analyzed using structural equation modeling (SEM) and partial least squares (PLS). The test findings demonstrate that the certification program motivates teachers, which enhances teacher performance by recognizing competence and ensuring financial security. Teachers with certifications are more active in training, focused, and deliver high-quality instruction. Incentives based on performance are also crucial for raising teacher motivation. These findings highlight the value of incentives and certification in raising educational standards through dedicated and financially secure teachers.